2011
DOI: 10.1016/j.beth.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Nursing Home Residents' Activity Participation and Affect as a Function of Staff Engagement

Abstract: Behavioral interventions for depression target activity engagement and increased positive reinforcement, particularly from social interaction. Nursing homes provide limited opportunity for meaningful social engagement, and have a high prevalence of depression. Often residents obtain most of their social contacts from staff members. We present intra-individual correlations among positive staff engagement, resident affect, and resident activity participation from behavior stream observations of residents who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…For instance, antecedent events such as prompts to engage in an activity (Brenske, Rudrud, Schulze, & Rapp, 2008;Engelman, Altus, & Mathews, 1999), activity prompts that include positive social attention (Polenick & Flora, 2011), or the presentation of activity materials in a salient location may momentarily establish the reinforcing effectiveness of activity engagement or social interaction, and may evoke behaviors associated with these events (Michael, 1993). Positive staff engagement has been significantly correlated with levels of interest, pleasure, and participation during activities for older nursing home residents (Meeks & Looney, 2011); thus, the social engagement of caregivers or family members may further increase activity participation and enjoyment. Embedding choice-making opportunities (Fisher, Thompson, Piazza, Crosland, & Gotjen, 1997) within activity scheduling is another area for exploration, in that this may increase the reinforcement value of activities.…”
Section: Directions For Future Investigationmentioning
confidence: 99%
“…For instance, antecedent events such as prompts to engage in an activity (Brenske, Rudrud, Schulze, & Rapp, 2008;Engelman, Altus, & Mathews, 1999), activity prompts that include positive social attention (Polenick & Flora, 2011), or the presentation of activity materials in a salient location may momentarily establish the reinforcing effectiveness of activity engagement or social interaction, and may evoke behaviors associated with these events (Michael, 1993). Positive staff engagement has been significantly correlated with levels of interest, pleasure, and participation during activities for older nursing home residents (Meeks & Looney, 2011); thus, the social engagement of caregivers or family members may further increase activity participation and enjoyment. Embedding choice-making opportunities (Fisher, Thompson, Piazza, Crosland, & Gotjen, 1997) within activity scheduling is another area for exploration, in that this may increase the reinforcement value of activities.…”
Section: Directions For Future Investigationmentioning
confidence: 99%
“…, Reed ). The relationship between NH staff attention and NH patients' affect and activity participation have been assessed among depressed NH patients, showing that positive staff engagement was significantly related to patients' interest, activity participating, and pleasure (Meeks & Looney ). These results suggest that staff behaviour and engagement could be a reasonable target for interventions to increase positive affect among NH patients (ibid.…”
Section: Introductionmentioning
confidence: 99%
“…Some could claim that these relationships might lead to biased data, as respondents may wish to please staff and tell them 'what they want to hear'. We found, however, that through these bonds research staff found more enjoyment, resulting in better job performance and high quality data (Meeks & Looney, 2011).…”
Section: Research Respondentsmentioning
confidence: 94%